2005
DOI: 10.1073/pnas.0500299102
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into the interaction and activation of histone deacetylase 3 by nuclear receptor corepressors

Abstract: SMRT (silencing mediator of retinoid acid and thyroid hormone receptor) and NCoR (nuclear receptor corepressor) are transcriptional corepressors that play an essential role in the regulation of development and metabolism. This role is achieved, in part, through the recruitment of a key histone deacetylase (HDAC3), which is itself indispensable for cell viability. The assembly of HDAC3 with the deacetylase activation domain (DAD) of SMRT and NCoR is required for activation of the otherwise inert deacetylase. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
97
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(101 citation statements)
references
References 43 publications
4
97
0
Order By: Relevance
“…Interestingly, the second SANT motif is part of a histone-interacting domain and functions synergistically with the DAD to promote histone deacetylation (Yu et al, 2003). The DAD of N-CoR/SMRT binds both the aminoand carboxy-termini of HDAC3 (Guenther et al, 2001) and forms a unique four-helical structure (Codina et al, 2005). The requirement for an intricately folded HDAC3 surface for interaction with the corepressors might allow for better regulation of its activity and prevent ectopic functions.…”
Section: Regulation Of Hdac3 Activitymentioning
confidence: 99%
“…Interestingly, the second SANT motif is part of a histone-interacting domain and functions synergistically with the DAD to promote histone deacetylation (Yu et al, 2003). The DAD of N-CoR/SMRT binds both the aminoand carboxy-termini of HDAC3 (Guenther et al, 2001) and forms a unique four-helical structure (Codina et al, 2005). The requirement for an intricately folded HDAC3 surface for interaction with the corepressors might allow for better regulation of its activity and prevent ectopic functions.…”
Section: Regulation Of Hdac3 Activitymentioning
confidence: 99%
“…12 Interestingly, a DAD mutation K449A which was inoffensive to HDAC3:DAD complex formation also abolished deacetylase activity. 16 As K449 is close to the IP4 binding site, the K449A mutation may inactivate the deacetylase via mediation of IP4-HDAC3 interactions, which would suggest that IP4 plays an additional role in the activation of HDAC3, aside from stabilizing the HDAC3:DAD complex. Here, we examine the structural ensemble of HDAC3, specifically: (i) how does this ensemble of HDAC3 structures change between the active HDAC3:DAD:IP4 complex and the inactive apo HDAC3 state?…”
Section: Introductionmentioning
confidence: 99%
“…NCoR (nuclear corepressor 1) and the homologous protein SMRT (silencing mediator or retinoic and thyroid hormone receptors or NCoR2) were identified by their interaction with unliganded thyroid hormone receptors (TRs) and retinoic acid receptors (2, 3), although later studies demonstrated that they also could bind to other transcription factors (4). NCoR and SMRT belong to large complexes that contain histone deacetylases (HDACs), thereby inducing chromatin compaction and gene silencing (4)(5)(6)(7). Although these corepressors interact with multiple HDACs, HDAC3 plays a key role in mediating their actions (8,9) and is essential for repression by TRs (10,11).…”
mentioning
confidence: 99%